PENGARUH STRATEGI KOMUNIKASI MANAJEMEN BISNIS DIGITAL TERHADAP OPTIMISME PENGUSAHA UMKM DI DKI JAKARTA - Herlina Herlina; Yohanes Probo Dwi Sasongko; Teguh Hidayatul Rachmad; Kho Gerson Ralph Manuel (Master of Communication Science Program, Universitas Diponegoro, 2023)
The Indonesian government has launched a MSME (Micro, Small and Medium Enterprises) go digital program. Government support for MSMEs has had an impact on the increasingly rapid development of MSME digital businesses. Especially in DKI Jakarta, many MSMEs have collaborated with technology through e-commerce. MSME digital businesses are increasingly mushrooming, causing digital business competition to become increasingly fierce, requiring MSME business entrepreneurs to think creatively and actively survive in facing challenges. Therefore, running a digital business for MSMEs requires a digital business management communication strategy that can provide direction and positive reinforcement for MSME business entrepreneurs to continue to survive in facing challenges. The objectives of this research are 1) to find out how digital business management communication strategies influence the optimism of business entrepreneurs in facing challenges; 2) to find out how to implement MSME digital business management communication strategies; 3) to find out how an optimistic attitude is formed in carrying out MSME digital business processes. This type of research is quantitative using an exploratory causality method. The research data is secondary data taken from 52 MSME business entrepreneurs in DKI Jakarta. The sampling technique was carried out incidentally. The research results show that: 1) there is a positive and significant influence of digital business management communication strategies on the optimistic attitude of MSME entrepreneurs with a contribution of 40.9% and the remaining 59.1% is explained by other variables; 2) digital business management communication strategy in running MSME businesses, namely business entrepreneurs in DKI Jakarta have implemented a proportional or balanced business communication strategy, namely planning at 24.15%; organizing by 25.20%; actuating by 23.65% and controlling by 27.00%; 3) the attitude of optimism that MSME entrepreneurs have in running a business is classified as proportional, namely permanence at 33.71%, pervasiveness at 32.58%, and personalization at 33.71%